Effect of Dry, Vacuum, and Modified Atmosphere Ageing on Physicochemical Properties of Roe Deer Meat - Natalia Kasałka-Czarna; Róża Biegańska-Marecik; Jędrzej Proch; Aleksandra Orłowska; Magdalena Montowska (Polish Journal of Food and Nutrition Sciences)
Consumers around the world are choosing sustainable and unprocessed foods. Roe deer meat, due to the natural origin, is a source of organic and healthy meat. The selection of suitable storage conditions and times plays an important role in a deterioration of the meat's functional and nutritional values. The knowledge about oxidation processes in roe deer meat stored and packed deploying different methods is limited. The main aim of this study was therefore to investigate the effect of storage method on the physicochemical properties of musculus longissimus thoracis et lumborum (LTL), musculus biceps femoris (BF), and musculus vastus lateralis (VL) of roe deer. The muscles were stored either dry (DRY-AGED), vacuum-packed (VAC), or packed under modified atmosphere (MAP) for 21 days. The quality of roe deer meat was assessed based on chemical composition, technological properties, pH values, water activity, colour, and oxidation processes of proteins and lipids. Roe deer meat had high protein (216.5–228.6 g/kg) and low fat content (17.1–25.8 g/kg). Both DRY-AGED and VAC contributed to improving meat tenderness during storage, while the Warner–Bratzler shear force of the MAP muscles increased. The high-oxygen conditions during MAP storage strongly induced the oxidation processes; an average increase of 1263% for thiobarbituric acid reactive substance (TBARS) level and 155% for protein carbonyl content on day 21. Vacuum packaging and dry-ageing are recommended methods for storing roe deer meat. The high oxygen atmosphere negatively affected the quality of this game species. It carries the risk of increased oxidation of proteins and lipids which may promote the formation of potentially detrimental compounds.